(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the efficacy of extracorporeal shockwave lithotripsy versus ureteroscopic intracorporeal lithotripsy with lithoclast for the treatment of proximal ureteric calculi. Subjects and Methods: The study included 87 patients with 8-15 mm proximal ureteric calculi .ESWL was performed in 45 patients and ureteroscopic lithotripsy in 42 patients. ESWL was performed by Storz Modulith lithotripter on out-patient basis. Ureteroscopy plus pneumatic lithotripsy was performed under anesthesia on in-patient basis. Results: Stone free rate in ESWL group was 64%. Ureteroscopic intracorporeal lithotripsy resulted in stone free rate of 79%. The difference was not considered statistically significant (p>0.1). No major complications were encountered in either group. Conclusions : In the absence of ancillary aids which prevent stone migration,Ureteroscopic lithotripsy is only marginally better( but statistically insignificant) than ESWL for treating upper ureteric calculi.. In fact these two modalities complement each other.